Incremental Load Respiratory Muscle Training Improves Respiratory Muscle Strength and Pulmonary Function in Children with Bronchiectasis - Xiaolong Chen; Shidong Hu; Xiaohui Jia; Bingbing Zeng (Canadian Respiratory Journal)
Background and Objective. To explore the effect of respiratory muscle training on children with bronchiectasis. Methods. Participants underwent respiratory muscle training for 24 weeks. The main results were changes in respiratory muscle strength and pulmonary function indices (forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), FEV1/FVC, peak expiratory flow rate (PEF), forced expiratory flow 25–75% (FEF25–75%), and maximal midexpiratory flow 75/25 (MMEF75/25)) before, 12 weeks after, and 24 weeks after the intervention. The secondary outcomes were changes in the exercise load and work rate, exercise work, Leicester Cough Questionnaire (LCQ) scale, and Fatigue Severity Scale (FSS). Results. Compared with before the intervention, after 24 weeks of respiratory muscle training, the maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP) were significantly enhanced (P<0.05), while FVC, FEV1, and PEF were significantly increased (P<0.01). FEF25–75 and MMEF75/25 values showed significant improvement compared to those before training (P<0.05). The exercise loading, work, and exercise work rate of expiratory muscle training were significantly improved compared to those before intervention (P<0.05). The LCQ score increased significantly (P< 0.001), and the FSS score decreased significantly (P< 0.001). Conclusion. Incremental load respiratory muscle training effectively improved children’s lung function over the long term, improved the strength of their inspiratory and expiratory muscles, and improved their quality of life.